ARCHITECTURE FOR UNDERSTANDING THE AUTOMATED IMAGINARY: A WORKING QUALITATIVE METHODOLOGY FOR RESEARCH ON POLITICAL BOTS - Abokhodair, Norah; Woolley, Samuel; Howard, Philip; McDonald, David (AoIR Selected Papers of Internet Research, 2015)
Social media – especially social networking sites – have substantially transformed the ways in which people discuss current affairs and obtain political news and information. Because of increased affordances for building and maintaining social connections, young people are better able to cultivate a political identity and engage civically in both authoritarian and democratic regimes [1]. Activist causes and democratic movements have been born, organized and disseminated on sites including Facebook, Twitter, Weibo, and YouTube [2]. Like any technology, though, the interfaces, applications, and modes of communication on social networking sites are in constant negotiation, transformation, and repurposing – and by a wide variety of social and political actors.